MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PERUBAHAN WUJUD BENDA MELALUI PROBLEM BASED LEARNING - Isnaini Choirun Nadhiro; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
This research was conducted with the aim of knowing student learning outcomes using the Problem Based Learning model. This research uses a classroom action research (PTK) and quantitative descriptive model. This PTK step consists of 2 cycles, each cycle is completed during one week. The research subjects were students in class 4 of the first semester of the 2023/2024 academic year. The instruments applied in the activities are written tests, documentation and observation, while the evaluation focuses on test and non-test based processes and results. The research results show that the use of Problem Based Learning (PBL) and concrete object media can improve student learning outcomes. This can be seen in the formative value which increased sharply, from 80% in cycle I and increased to 93% in cycle II. The cycle ends when learning completeness reaches more than 85% in cycle II.